L’arco dei foschi di berta, l’architettura die foro di traiano a nord della basilica ulpia e l’iscrizione CIL VI, 966 (=31215) - Meneghini, Roberto (Römische Mitteilungen, 2024)
For scholars dealing with the area around Trajan’s Column, one of the most elusive elements has always been the so-called Arco dei Foschi di Berta. The monument, whose precise position and appearance are unknown, appears in some notarial documents of the late Middle Ages and the Renaissance. From these, it is possible to place it in the medieval and modern topography of the area and verify its relationship with the architecture of the Forum of Trajan. The Arch turns out to be one of two architectural elements of this type through which one accessed the pair of monumental staircases positioned against the northern side of the so-called Libraries. Through these staircases one could reach the upper floor of the arcades of the courtyard of Trajan’s Column and the Basilica Ulpia. The double inscription CIL VI, 966 = 31215 probably decorated the attics of the two arches.